Objective response rate of placebo in randomized controlled trials of anticancer medicines. (January 2023) - Sachdev, Arushi; Sharpe, Isobel; Bowman, Meghan; Booth, Christopher M.; Gyawali, Bishal
Summary: Background: Spontaneous regression of advanced solid tumors is infrequent but may occur. Quantifying response rates from placebo in cancer drug trials may provide important information for physicians, patients, and regulators. We aimed to provide a pooled placebo response rate from drug trials in advanced solid tumors. Methods: We pooled the overall response rate (ORR), complete response rate (CR) and partial response rates (PR) in the placebo arm of placebo-controlled randomized controlled trials (RCTs) of cancer drugs for advanced solid tumors published during 2015–2021 using random-effects model. Findings: 45 phase 3 RCTs including 5684 patients on placebo met our inclusion criteria and formed the study cohort. The pooled overall ORR, CR and PR rates in the placebo arm were 1% (95% CI, 0%–2%), 0% (95% CI, 0%–0%), and 1% (95% CI, 0%–2%) respectively. Higher placebo responses were observed in prostate cancer and sarcoma trials. Interpretation: Overall, 1% patients with advanced solid tumors can expect to achieve some response even in absence of treatment. However, complete regression without treatment is extremely rare, almost zero percent. This information will be helpful to patients in their decisions, as well as regulators in evaluating cancer drugs' efficacy based on response rates alone. Funding: None.